A sentinel in Mitraclip intervention: Catch the enemy!. Issue 6 (4th October 2018) - Calcagno, Simone; Cimino, Sara; Cerbelli, Bruna; Sardella, Gennaro
Abstract: Cerebral ischemic lesions occurring during transcatheter valve interventions are common feared complications and the use of filter device seems to reduce their incidence. We report the case of an 84‐year old female patient with severe mitral regurgitation undergoing MitraClip. During the trans‐esophageal echocardiography (TEE)‐guided procedure was detected the presence of a little fibrin strand adherent to the steerable guide catheter for which we decided to implant the Claret CE Pro (Claret Medical, Inc. Santa Rosa, CA, USA) cerebral protection device and to continue the procedure during which the thrombus disappeared. At the end of the procedure a big thrombus was detected in the distal filter. The histologic analysis of the debris captured by the filters showed the presence of a thrombus, compatible with the image identified by TEE.